Reliability assessment of island multi‐energy microgrids - Marcos Santos (Wiley, 2021)
Abstract Multi‐energy microgrids could result in more flexibility and increase reliability by interconnecting networks. Electricity and gas networks exhibit very different dynamic behaviours in response to a fault or failure. Gas networks have built‐in energy storages that can continue to provide a reliable supply if gas inputs to the system are compromised. This study presents a novel reliability assessment method applied to multi‐energy microgrids; the method combines an incidence matrix analysis that identifies the connectivity between sources and load points with a sequential Monte Carlo simulation and generation adequacy evaluation. A case study is conducted by using an electricity‐gas microgrid. The electricity network is a multi‐sourced grid, whereas the gas network is supplied by a biogas plant. The linepack (gas stored along the pipelines) is modelled to account for the slower gas dynamics. The proposed method is evaluated on a real‐world electricity distribution network in Austria. The results indicate the reliability benefits of forming a multi‐energy microgrid.